2022
DOI: 10.1093/nar/gkac1082
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the unique multifaceted interaction of DPPA3 with the UHRF1 PHD finger

Abstract: Ubiquitin-like with PHD and RING finger domain-containing protein 1 (UHRF1)-dependent DNA methylation is essential for maintaining cell fate during cell proliferation. Developmental pluripotency-associated 3 (DPPA3) is an intrinsically disordered protein that specifically interacts with UHRF1 and promotes passive DNA demethylation by inhibiting UHRF1 chromatin localization. However, the molecular basis of how DPPA3 interacts with and inhibits UHRF1 remains unclear. We aimed to determine the structure of the mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Thus, we identified the corresponding region of hDPPA3 by sequence alignment (residues 81-118 [hDPPA3 81-118 ] (Figure 1a and 1b), and evaluated whether this region binds to the human UHRF1 PHD finger, residues 299–366 (hPHD). Isothermal titration calorimetry (ITC) demonstrated that hDPPA3 81-118 could bind to hPHD with a K d of 0.868 μM (Figure 1c), which is approximately 30-fold weaker than the binding affinity between mDPPA3 and mPHD ( K d = 0.0277 μM) 29 . The binding affinity of hDPPA3 to hPHD 81-118 is comparable with the previously reported binding affinity between hPHD and the histone H3 N-terminal tail (residues 1–15; K D = 1.7 μM) or PAF15 (residues 1–10; K D = 2.2 μM) 17,31 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, we identified the corresponding region of hDPPA3 by sequence alignment (residues 81-118 [hDPPA3 81-118 ] (Figure 1a and 1b), and evaluated whether this region binds to the human UHRF1 PHD finger, residues 299–366 (hPHD). Isothermal titration calorimetry (ITC) demonstrated that hDPPA3 81-118 could bind to hPHD with a K d of 0.868 μM (Figure 1c), which is approximately 30-fold weaker than the binding affinity between mDPPA3 and mPHD ( K d = 0.0277 μM) 29 . The binding affinity of hDPPA3 to hPHD 81-118 is comparable with the previously reported binding affinity between hPHD and the histone H3 N-terminal tail (residues 1–15; K D = 1.7 μM) or PAF15 (residues 1–10; K D = 2.2 μM) 17,31 .…”
Section: Resultsmentioning
confidence: 99%
“…Our previous NMR structural analysis of mDPPA3 complexed with mUHRF1 PHD (mPHD) revealed that residues 85–118 of mDPPA3 are essential for its interaction with mPHD (Figure 1b and 2b) 29 . Thus, we identified the corresponding region of hDPPA3 by sequence alignment (residues 81-118 [hDPPA3 81-118 ] (Figure 1a and 1b), and evaluated whether this region binds to the human UHRF1 PHD finger, residues 299–366 (hPHD).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DPPA3/Stella/Pgc7, an intrinsically disordered protein without a recognizable functional domain, forms a tight complex with UHRF1, which regulates the maintenance of DNA methylation along with Dnmt1 (Li et al, 2018). DPPA3 undergoes a “disorder‐to‐order” structural transformation and tightly associates with the PHD domain of UHRF1 (Hata et al, 2022). This interaction results in the dissociation of UHRF1 from histones and subsequent nuclear export of this chromatin modifier.…”
Section: Molecular Mechanisms Of Nondomain Biopolymersmentioning
confidence: 99%